The Engagement in The Tradition of Samin Tribe Community: Islamic Law Perspective - Muhammad Chairul Huda; Hany Rahma Septiasih; Nastangin Nastangin (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The engagement in the Samin society tradition in Kemantren Village, Kedungtabun District, Blora Regency is known as nyuwita-ngawula. They still apply some ideologies that are believed to come from their ancestors. This research aims to reveal the procedures and meanings behind the nyuwita-ngawula tradition from the perspective of legal culture and Islamic law. This research is field research and the approach used is qualitative. Data collection techniques used observation and interviews. The data obtained were then analyzed by the descriptive analysis method. The result of the research is the nyuwita-ngawula tradition was carried out by a groom who would propose to one of the women he had chosen by having sex in one room like husband and wife, where they did the engagement with the aim of getting a match between the brides. When an agreement is reached, the marriage can proceed. If this is not done, the engagement based on the Samin ethnicity is considered void and cannot be continued to the marriage level. However, there is a shift in action as the Samin society understands the values ​​of Islamic law. Currently, the Samin tribe's customary engagement is to hold a marriage using a judge's guardian. This is done because the guardian of the prospective wife does not approve if before marriage they do not carry out the marriage custom of nyuwita-ngawula in the Samin tribal society.